International Climate Change Scenario and its Implications for Nepal: A Mountain Perspective - Shrestha, Basanta (NCWA Annual Journal, 2026)
Climate change has emerged as one of the defining challenges of the twenty-first century, reshaping global development trajectories, geopolitical relations, and the foundations of human security. While climate change is a global phenomenon, its impacts are unevenly distributed, disproportionately affecting vulnerable regions and communities. Mountain regions, particularly the Hindu Kush Himalaya (HKH) region, are among the most sensitive and least resilient to climate-induced stresses. Nepal, located at the heart of the Himalayas, exemplifies this paradox: it contributes negligibly to global greenhouse gas emissions yet bears a disproportionate burden of climate impacts. This article examines the international climate change scenario and its implications for Nepal from a mountain-centric and policy-oriented perspective. It explores global climate trends, mountain-specific vulnerabilities, Nepal’s leadership role in advancing the mountain agenda, and the relevance of climate change to sustainable development. Drawing from regional cooperation experiences in the HKH region and insights gained through professional engagement at the International Centre for Integrated Mountain Development (ICIMOD), the paper highlights the importance of climate diplomacy, global negotiations, climate finance, and adaptation strategies. It also addresses emerging issues such as loss and damage, climate-induced disasters, and the need for resilience-building in Nepal. This paper aims to inform policy discourse and contribute to Nepal’s strategic engagement in international climate forums and dialogues.